La Identidad cultural en el proceso de enseñanza – aprendizaje en el CECIB “Sergio Núñez - Caillagua Caisa, Olga Fabiola (2022)
The present research tries to know the relationship between cultural identity and the teaching-learning process of the students of Basic Education of the CECIB "Sergio Núñez" to achieve a teaching-learning process based in the customs and traditions respect, to put up a favorable climate inside the classroom and the community, doing integral human beings capable of feeling, doing and be, with the strengthening aim participation in cultural activities guided at developing and strengthening critical knowledge and self-thinking, from basic education, from culture and the ability to interpret products and manifests cultural activities of the CECIB "Sergio Núñez", which enables students to freely express what they feel. The present investigation has a quantitative approach which allowed to collect data and analyze variables. The research also allowed Basic Education students, through the practice of didactic strategies, to improve their self-esteem through the acquisition such as; habits, skills, knowledge and abilities, stimulating the freedom, confidence and security, which helped develop the emocional intelligence. The research helped to complement the cultural identity with the teaching-learning process, since learning will be more efficient with the recognition of the cultural identity of the community as an educational model that encourages teachers make to use of their authentic vocation, based on understanding and tolerance, together with its values and virtues.